The impact of personal values on judgments of ethical behaviour in the workplace - Finegan, Joan (Journal of business ethics, 1994)
This study examines how our personal values influence our judgment of the morality of some workplace behaviours. Sixty-nine undergraduates were asked to rank order separately Rokeach's instrumental and terminal values in terms of their importance as guiding principles in their life. Subjects then read four scenarios, each of which described ethically questionable behaviour of the sort that might be encountered in business. They were then asked to rate whether or not the behaviour of the person described in the scenario was ethical, and whether or not they had any intentions to rectify the situation. People with different value hierarchies perceived the targeted behaviours differently. For example, subjects who valued “honesty” perceived the behaviour as more immoral than subjects who did not value honesty. While the ranking of the instrumental valuehonesty was the best predictor of people's judgments about the morality of the behaviour, their ranking of the instrumental valueambition was the best predictor of their behavioural intentions.